WORKING CAPITAL MANAGEMENT, LIQUIDITY AND COMPANY SIZE ON CAPITAL STRUCTURE - Sejati, Fajar Rina; Pertiwi, Dian; Adawiyah, Asrindah Nur (Applied Accounting and Management Review (AAMAR), 2024)
This research was conducted to examine Working Capital Management, Liquidity and Company Size on Capital Structure in Basic Industrial and Chemical Companies listed on the IDX for the 2014-2017 period. The sample studied was 16 companies. Data were analyzed using Path analysis with the help of the SPSS version 25 computer program. The research results showed that Working Capital Management, Liquidity and Company Size had a significant negative effect on Capital Structure.